2014
DOI: 10.1037/a0036091
|View full text |Cite
|
Sign up to set email alerts
|

Classroom-level predictors of the social status of aggression: Friendship centralization, friendship density, teacher–student attunement, and gender.

Abstract: This study investigated moderating effects of classroom friendship network structures (centralization and density), teacher-student attunement on aggression and popularity, and gender on changes in the social status of aggression over 1 school year. Longitudinal multilevel analyses with 2 time points (fall and spring) were conducted on a sample of 856 fourth and fifth graders from 45 classrooms. Aggressive boys lost social status over time in classrooms where friendship networks were egalitarian (not centraliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
78
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(85 citation statements)
references
References 66 publications
(102 reference statements)
4
78
2
1
Order By: Relevance
“…In an early study of teacher attunement, Hamm et al (2011) found that greater teacher-student attunement was positively related to students' sense of belonging at school, students' willingness to protect peers being bullied, and students' sense that peers would stand up for them if they were bullied. Others have measured teacher attunement as teachers' awareness of their students' characteristics and behavior and found that when teachers had high levels of attunement to aggression, the popularity status of highly aggressive boys decreased over time (Ahn & Rodkin, 2014). These findings underscore the impact teacher attunement can have on their students' peer experiences (e.g., Norwalk, Hamm, Farmer, & Barnes, 2015).…”
Section: Teacher Attunementmentioning
confidence: 99%
“…In an early study of teacher attunement, Hamm et al (2011) found that greater teacher-student attunement was positively related to students' sense of belonging at school, students' willingness to protect peers being bullied, and students' sense that peers would stand up for them if they were bullied. Others have measured teacher attunement as teachers' awareness of their students' characteristics and behavior and found that when teachers had high levels of attunement to aggression, the popularity status of highly aggressive boys decreased over time (Ahn & Rodkin, 2014). These findings underscore the impact teacher attunement can have on their students' peer experiences (e.g., Norwalk, Hamm, Farmer, & Barnes, 2015).…”
Section: Teacher Attunementmentioning
confidence: 99%
“…Teachers who are attuned to the social dynamics of their students, such as which children affiliate together in peer groups, tend to have classrooms characterized by more positive social climates, with students that report a greater sense of school belonging and a greater willingness to defend victims of bullying (Hamm et al, 2011). Intervention efforts to improve teacher attunement have demonstrated positive effects on teachers' ability to identify the peer groups of students identified as bullies (Farmer, Hall, Petrin, Hamm, & Dadisman, 2010); in turn, when teachers and students agree which children in their classrooms are aggressive, the social status of aggressive children diminishes over time (Ahn & Rodkin, 2014). Unfortunately, teacher attunement to bully-victim dyads is generally low, particularly as the number of students in a classroom increases (Ahn, Rodkin, & Gest, 2013).…”
mentioning
confidence: 99%
“…The average number of links per node is varied at two and six, again aiming to reflect a reasonable low and high range of ties per node seen in practice (Dijkstra, Cillessen, & Borch, 2013; Ahn & Rodkin, 2014). Both of these types of conditions reflect similar values to what is commonly seen in empirical applications, such as the one that follows in this article.…”
Section: Simulation Studymentioning
confidence: 99%